A thematic analysis of narrative elements and technical aspect in “Blood Flower” (2023) based on film reviews - Zairul Anuar Md. Dawam; Addley Bromeo Bianus; Rosli Sareya; Imelda Ann Achin (Akademi Seni dan Teknologi Kreatif (ASTiF), Universiti Malaysia Sabah, 2025)
This study conducts a thematic analysis of the narrative elements and technical aspects of the film Harum Malam or "Blood Flower" (2023) directed by Dain Said, based on reviews written by various critics. The analysis aims to evaluate the strengths and weaknesses of the film's narrative elements and technical aspects. A qualitative approach is employed, using thematic analysis with a coding system to categorize the narrative elements mentioned in the reviews. A total of 26 reviews were collected from various online sources. The study finds that reviewers have offered a range of insights into the film's narrative and technical aspects. According to the reviews, the film's premise and themes are unique and engaging. Technical aspects such as visual effects (VFX) and sound design are also praised. However, the film exhibits notable weaknesses in narrative elements, such as character development and plot structure, which impact the overall storytelling. The thematic analysis based on these reviews provides a more objective understanding of the narrative elements in "Blood Flower" and offers guidance for filmmakers aiming to create improved films in the future.